Eksplorasi Etnomatematika Dan Geometri Pada “Rumoh Aceh” - Nur Azmi; Siti Nurhaliza; Darajatul Ula; Dwi Syifa; Suhaimi; Rossa Aprillia (Ar-Riyadhiyyat: Journal of Mathematics Education, 2021)
Culture and religion are two very sacred things that cannot be separated in the life of the Acehnese people. Every activity in the life of the Acehnese is inseparable from religious values ​​that have even become culture, one of which is applied in the "rumoh Aceh" building. The aceh house building has an Islamic philosophy and a legacy of living order in each of its buildings and ornaments. Even without realizing it, there are perfect mathematical activities in Acehnese houses, starting from numbers, traditional calculations without measuring tools, and structured similarities without knowledge of formulas and geometry. Besides having an Islamic philosophy, the Acehnese house also has beautiful carvings that have high aesthetic value and balanced and perfect measurements. As an educator, the study of mathematical activities at the Rumoh Aceh cultural site is interesting to explore, in order to make mathematics more meaningful to learn. Nowadays, linking culture and mathematics has been growing, which is known as ethnomathematics. It is proper that ethnomathematics is explored and presented in learning to make mathematics interesting to learn, besides that with the exploration of culture in mathematics, knowledge about regional culture will not be destroyed by time for future generations. This paper aims to explore the concepts of mathematics and geometry as well as the philosophical meanings contained in Acehnese houses which are described through design and building elements in terms of ethnomathematical activities. Through exploration, literature study, observation and documentation on Acehnese houses, it can be concluded that ethnomathematical activities in the design of Acehnese houses include the concept of numbers, measurements, and geometric concepts including: the number of pillars, steps, walls, roofs and floors (build up). planes and shapes), the concept of angles, lines (horizontal, vertical, and perpendicular) and geometric transformations. The philosophical meaning contained in the Aceh house construction is to always face the Qibla, withstand floods and storms and glorify hosts and guests.